Flexible photonic topological insulator - Gao, Zhen (2019)
A mechanically flexible photonic topological insulator that supports robust topological photonic states on a curved surface is experimentally demonstrated. Spatial topologies achieved by folding the flexible photonic topological insulator serve as a new freedom to manipulate the propagation of topological photonic states. This work bridges the gap between the emerging field of topological photonics and the technologically promising field of flexible photonics.